Avaliação da presença de cães e suas implicações na saúde física e emocional de crianças de cinco e seis anos de idade, em Belo Horizonte, MG - Rachel Capanema Ferreira Mendonca (2011)
This study was an observational study with cross structure, aimed to verify some aspects association between quality of life of children and the presence of dogs. Having cats included in the evaluation in order to avoid bias in the survey, questionnaires were distributed to the data that arose later produced the multiple linear regression models which verifies some associations between the child's interaction with the dog, and their impact on their quality of life. As a result of the study found improved quality of life resulting from this contact, especially the act of playing with the dog, also the lowest quality of life of children allergic to dogs and cats. In conclusion it was realized that living with the dog can be beneficial to the child.